Towards the automatic crystal structure solution of nucleic acids: automated model building using the new CAB program. Issue 12 (30th November 2021) - Cascarano, Giovanni Luca; Giacovazzo, Carmelo
Abstract : The new CAB automatic model‐building program is described and compared with other automated model‐building techniques. Abstract : CAB, a recently described automated model‐building (AMB) program, has been modified to work effectively with nucleic acids. To this end, several new algorithms have been introduced and the libraries have been updated. To reduce the input average phase error, ligand heavy atoms are now located before starting the CAB interpretation of the electron‐density maps. Furthermore, alternative approaches are used depending on whether the ligands belong to the target or to the model chain used in the molecular‐replacement step. Robust criteria are then applied to decide whether the AMB model is acceptable or whether it must be modified to fit prior information on the target structure. In the latter case, the model chains are rearranged to fit prior information on the target chains. Here, the performance of the new AMB program CAB applied to various nucleic acid structures is discussed. Other well documented programs such as Nautilus, ARP / wARP and phenix.autobuild were also applied and the experimental results are described.